2014
DOI: 10.1007/s10853-014-8730-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy, corrosion resistance, and cytotoxicity studies of copper-substituted carbonated hydroxyapatite coating on titanium substrate

Abstract: This work elucidated the antibacterial efficacy, corrosion resistance, and cytotoxicity of electroplated copper-substituted hydroxyapatite (CuHAP) coating on titanium (Ti). The fabricated CuHAP coatings were characterized by scanning electron microscopy, energydispersive X-ray analysis spectroscopy, Fourier transform infrared spectroscopy, and X-ray diffraction studies. The CuHAP coating had needle-like apatite crystals, the doping of Cu 2? into HAP reduced porosity, and the coating became denser. The CuHAP cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 56 publications
(95 reference statements)
2
32
0
Order By: Relevance
“…As in its natural form, it is possible to incorporate different ions into the synthetic HA lattice. Based on this, scientists frequently study on doping and co‐doping of various ions into the structure of HA with the purpose of tailoring the properties of HA and therefore functionalizing implant surfaces and bone substitutes …”
Section: Introductionmentioning
confidence: 99%
“…As in its natural form, it is possible to incorporate different ions into the synthetic HA lattice. Based on this, scientists frequently study on doping and co‐doping of various ions into the structure of HA with the purpose of tailoring the properties of HA and therefore functionalizing implant surfaces and bone substitutes …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the easiness of atomic doping or substitution in HA reveals its potential to be used in various clinical cases [4][5][6]. Most importantly, it has been shown that inorganic antibacterial metallic ions (e.g., Ag, Cu, Zn, Sr) can be introduced into the HA lattice and improve its antibacterial properties [7][8][9][10][11][12][13][14]. However, there is a physical approach to antibacterial surface production.…”
Section: Introductionmentioning
confidence: 99%
“…Many different techniques are being used to synthesize Calcium Hydroxyapatite (CHAp) coatings on the substrate [4]. Plasma spraying is the only one approved by the Food and Drug Administration (FDA) [5].…”
Section: Introduction mentioning
confidence: 99%